Análise preliminar das manifestações sonoras e do habitat de Picumnus nebulosus Sundevall (Aves, Picidae) - Anjos,Luiz dos (1999)
Observations and recordings of Picumnus nebulosus Sundevall, 1866 were carried out at Santa Rita farm (21º15'S, 50º00'), municipality of Palmeira, state of Paraná, southern Brazil, from 1984 to 1991. The song of this species (0.25 s to 0.64 s total time) is composed by a series of four to six high pitched (6.3 to 7.8 kHz) and short (0.03 to 0.05 s) notes (n=23). The fight call is a series of very short notes emitted between 2 to 8 kHz during 0.23 s to 0.32 s (n=34). The drum, a sequence of pulses, is emitted during 3.5 to 7.2 s (n=42); the four sequences in the begining are composed by four pulses and the rest by three pulses. P. nebulosus was more abundant in forest patches than in continuous forest. It was usually watched foraging in branches 1 to 4 mm diameter at mid-level; foraging in bamboo, the most common habitat cited in the literature, was registered in less than 10% of the observations.